Distribution profile of iridoid glycosides and phenolic compounds in two Barleria species and their correlation with antioxidant and antibacterial activity - Singh, Shachi; Kumar, Mukesh; Dwivedi, Seema; Yadav, Anjali; Sharma, Sarika (Frontiers in Plant Science, 2023)
Barleria species are known for their medicinal properties from ancient times. Bioactive compounds have been isolated from leaves of the plant. However, other parts of a medicinal plants are also important source of active metabolite. Therefore, the objective of this study was to screen leaf, root, stem and inflorescence of two Barleria species, B. prionitis and B. cristata, with a rapid and effective metabolomic method. ESI-QTOF-MS/MS system with information dependent acquisition (IDA) method was used to collect high resolution accurate mass data (HRMS) on both the parent and their fragment ions. Iridoid glycosides and phenolic compounds were identified from all parts of the plants, showing variability in presence and abundance. Antioxidant and antibacterial activity was revealed in all organs. Some of the iridoid glycosides and phenolic compounds were found to be positively correlated with the tested biological activity. Principal component analysis of the chemical profiles showed variability in distribution of the compounds.